The neurosurgical outpatient clinic: comparison between accesses in public and private activities - Marta Menegatti; Nunzia Del Villano; Alba Scerrati; Francesco Travaglini; Luca Ricciardi; Giorgio Lofrese; Michele Alessandro Cavallo; Pasquale De Bonis (BMC, 2024)
Abstract Background Neurosurgical clinic assesses presence and extent of pathologies of central and peripheral nervous system or disorders affecting the spine, to identify most effective treatment and possible recourse to surgery. The aim of the study is to evaluate the appropriateness of request for a neurosurgical consult both in private and in public outpatient clinics. Materials and methods We collected and analyzed all the reports of outpatient visits of public and private clinic over a period between January and December 2018. Results There were 0.62% real urgent visits in the public sector and 1.19% in the private sector (p = 0.05). Peripheral pathologies represented 12.53% and 6.21% of pathologies evaluated in public and private sector respectively (p < 0.00001). In addition, 15.76% of visits in public lead to surgery, while they represented 11.45% in private (p = 0.0003). Conclusions No study is available comparing accesses of patients in neurosurgical outpatient clinics. In public clinic, visits are booked as urgent on the prescription of the general practitioner: in reality, only 5% of these visits were really confirmed as urgent by the specialist. Peripheral pathologies are more frequent in public clinic, while cranial pathologies are more frequent in private one. Patients with cranial pathologies prefer to choose their surgeon by accessing private clinic.